Cinnamomum impressinervium meisn.: antioxidant and antimicrobial activities - Bhatia, Lovkesh; Sharma, Amit; Kalra, Rishu; Kumar, Varun (Creative Pharma Assent, 2024)
Background: The Cinnamomum impressinervium (CI) Meisn. Tree, which belongs to the Lauraceae family and is endemic to India, is also called Assameses or Tejiya. Numerous pharmacological properties of this plant, including anti-tumor, anti-inflammatory, and antioxidant properties, have been demonstrated. Materials and method: This study examines the phytochemical profile of the leaf using qualitative and quantitative methods. Following the phytochemical analysis of the leaf, the antioxidant efficacy for scavenging free radicals (ABTS and DPPH) was measured. Using the agar well diffusion method, the antibacterial potential of the crude extract and its fractions (aqueous, methanolic, n-hexane, and chloroform) was investigated against six gram-negative, three gram-positive, and one fungal strain. Result and discussion: Antioxidant activities of various extracts viz: aqueous, hexane, chloroform, and ethanol were prepared and subjected to antioxidant and antimicrobial activities. Through qualitative analysis, several alkaloids, steroids, and flavones were identified. In the DPPH and ABTS assays, the aqueous extract had the most potent antioxidant activity, with IC50 values of 123.83±0.42 and 57.86±0.85 μg/mL, respectively. DNA nicking assay is a qualitative analysis that shows DNA protection from free radicals. All the extracts towards B. atropheous showed best inhibition activity but a maximum zone of inhibition was shown by aqueous extracts measuring 40 mm. Aqueous and methanolic extracts are completely inactive towards S. typhi. Conclusion: This study revealed the antioxidant and antimicrobial efficacy of various extracts of Cinnamomum impressinervium Meisn. Leaves In this paper, the antibacterial activity of leaf extracts from Cinnamomum impressinervium Meisn. were studied. The evaluated extracts showed varied levels of inhibitory zones against every tested bacterium.